As atribuições da biblioterapia desenvolvida em projetos - PASSOS, Sandy Larissa Souza dos (2019)
This paper works with the theme of Bibliotherapy developed in hospitals, considering that the field of therapeutic reading is still a subject rarely explored by professionals in the area. The research consisted in gathering and studying the concepts of hospital bibliotherapy, recognizing the benefits caused by the use of literature as a therapeutic activity that assists in conventional medical treatment, identifying the contribution of the librarian as a bibliotherapist and presenting bibliotherapeutic projects in Brazil and the United Kingdom , analyzing the details of the activities that are developed in each project and pointing out the methodology that they use to develop the bibliotherapy either in hospital units, shelters, resocialization units or school environments. Through the Brapci database, scientific articles were retrieved to support the work, gathering ideas from the main authors of the area, gathering the information obtained to elaborate this bibliographical and documentary research, identifying factors that have relevant features such as mediation of reading; stimulus to the habit of reading; encouragement to the debate and participation of the librarian as transforming agent.